Improvement of ASTM A53 Steel Durability Using Agrowastes as Carburizing Agent - Afolalu, Sunday Adeniran; Ikumapayi, Omolayo; Emetere, Moses; Ogedengbe, Temitayo (International Journal of Integrated Engineering, 2021)
The importance of steel in manufacturing and construction over the past century cannot be over-emphasized and easy accessibility couple with excellent mechanical properties make it preferable over others. However, the problem of durability has posed a serious concern as majority of steel application are meant for long term use. Several attempts have been made to improve the durability of steel in the past and increase of carbon content in low carbon steel was found to be a suitable agent. Although getting carbon is not the challenge rather obtaining it from a sustainable source that has zero environment impact. This research identified two separate agro-waste that has high carbon content the issue of sustainability brought about the development of carburizing agent from agro-waste that are easily accessible namely palm kernel and eggshell which is employed in this research. The use of agro-waste was found to be effective as there was notable increase in grain structure of the carburized steel when compared to the control sample without carburized agent in it.